2005
DOI: 10.1080/08120090500134514
|View full text |Cite
|
Sign up to set email alerts
|

Chemical U – Th – Pb monazite dating and the Proterozoic history of King Island, southeast Australia*

Abstract: The Proterozoic stratigraphy of Tasmania has some common aspects with South Australia but the Wickham Orogeny (760 Ma) has been a major contrasting feature.We have used chemical U-Th-Pb monazite dating to clarify the age relationships Monazites are typically concordant, with the measured common Pb component much less than the analytical error in electron probe micro -analysis (EPMA) (Cocherie et al. 1998, Scherrer et al. 2000. In-situ analysis and the high spatial resolution of EPMA allows the correlation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Albeit only a small island in Bass Strait, King Island predominately comprises Precambrian rocks and is situated in a key position with major implications for tectonic reconstruction in SE Australia. The oldest rocks of King Island are Mesoproterozoic metasediments that crop out at the southern tip of the island (Black et al, 2004;Berry et al, 2005;Calver, 2007). It is important to note here that no corresponding rocks are known in Tasmania and Victoria (Calver, 2007).…”
Section: Geology and Tectonic Settingmentioning
confidence: 98%
See 1 more Smart Citation
“…Albeit only a small island in Bass Strait, King Island predominately comprises Precambrian rocks and is situated in a key position with major implications for tectonic reconstruction in SE Australia. The oldest rocks of King Island are Mesoproterozoic metasediments that crop out at the southern tip of the island (Black et al, 2004;Berry et al, 2005;Calver, 2007). It is important to note here that no corresponding rocks are known in Tasmania and Victoria (Calver, 2007).…”
Section: Geology and Tectonic Settingmentioning
confidence: 98%
“…Palaeomagnetic evidence in the form of magnetic remanence (Li et al, 1997) has also been used. Geochemical investigations include apatite fission track (O'Sullivan et al, 2000) and detrital zircon age analysis (Berry et al, 2001), U-Th-Pb monazite dating (Berry et al, 2005(Berry et al, , 2007(Berry et al, , 2008) and a variety of other geochemical measurements (Reed et al, 2002;Clemens and Benn, 2010). Only a few interpretations rely on an integrated approach whereby multiple datasets are used to provide a tighter set of constraints (Cayley et al, 2002;Direen and Crawford, 2003;Teasdale et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Here the term 'Mawsonland' is formally introduced as a more succinct synonym to 'Mawson Continent.' The Albany-Fraser belt is truncated on its western end by the late Neoproterozoic Pinjarra orogen (Fitzsimons 2003) and on its eastern end by the Palaeozoic Lachlan-Thompson accretionary orogen (Li & Powell 2001), although some local vestiges of Mesoproterozoic orogeny or magmatism are documented in northern Queensland (Blewett & Black 1998) and around Tasmania (Berry et al 2005;Fioretti et al 2005). These truncations can provide important piercing points for Rodinia reconstructions, because the Albany-Fraser-Musgrave orogen contains, along its entire length, two episodes of tectonomagmatic activity dated at c. 1320 and c. 1200-1150 Ma (White et al 1999;Clark et al 2000).…”
Section: Australia 1 Mawsonlandmentioning
confidence: 99%
“…The study of the Tasmanian eclogite was undertaken to confirm if its zircons grew during collision-related eclogite facies metamorphism or whether they formed in some other event unrelated to high-pressure metamorphism. Although metamorphism at ~510 Ma has been shown by chemical U-Th-Pb monazite dating to be widespread in Tasmania (Berry et al, 2005) and therefore part of the Delamerian(-Tyennan) Orogeny, it has been assumed rather than demonstrated that the ~510 Ma SHRIMP U-Pb zircon age on eclogite in the Franklin Metamorphic Complex reflects the timing of high-pressure metamorphism. We have therefore undertaken rare earth element (REE) analysis of these zircons to see if they have a low HREE abundance and no negative Eu anomaly signature that is diagnostic of zircons grown during eclogite facies metamorphism (Rubatto, 2002).…”
Section: Introductionmentioning
confidence: 99%